Laju Pertumbuhan dan Penempelan Kerang Hijau (Perna viridis, Linn, 1789) - Yonvitner Yonvitner; Sutrisno Sukimin (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2009)
Green mussel inclusive of pelecypoda class of mollusc group that a lot of in coastal water like Jakarta Bay. Green mussel in Jakarta Bay has been culturing by society that used a collecting media that called bagan tancap.  The increasing of human being activity, also to increase of the bagan reach to 3000 unit. Information about the settling ability and growth of mussel in bagan it important to studied.  This research aims to know growth rate green mussel population and settling ability. To evaluate of growth used Bartalanfy plot and  FISAT II, 2003. Result of growth rate from 0,42 - 0,92 up at middle, infinity length reach 12, 73 cm. The settlement rate fastest in offshore for others site.